Foraminiferal biostratigraphy of Yadgar area, Muzaffarabad Azad Kashmir, Pakistan - Baig, Mirza Shahid; Munir, Munir-ul-Hassan (Journal of Himalayan Earth Sciences, 2007)
At Yadgar in Muzaffarabad Azad Kashmir, the Late Paleocene to Middle Eocene shallow water marine sequence overlies unconformably on the Cambrian carbonate unit of the Abbottabad Formation and includes the Hangu Formation, the Lockhart Limestone, the Patala Formation, the Margala Hill Limestone, the Chor Gali Formation and the Kuldana Formation. The Paleogene sequence is overlain by the Miocene Himalayan molasse of the Murree Formation. The genera Lockhartia, Ranikothalia, Assilina and Nummulites include Lockhartia tipperi (DAVIES), Lockhartia conditi (NUTTALL), Ranikothalia sindensis (DAVIES), Ranikothalia nuttalli (DAVIES), Assilina spinosa DAVIES and PINFOLD, Assilina subspinosa DAVIES and PINFOLD, Assilina laminosa GILL, Nummulites atacicus (LEYMERIE) and Nummulites mamillatus (FICHTEL and MOLL) are described and illustrated for the first time from the Upper Paleocene and Early to Middle Eocene beds in this region. The analyses of these larger benthic foraminifers suggest that the deposition of the Paleogene sequence occurred in a Neotethys warm and shallow marine environment in the Yadgar area, Muzaffarabad.